OTITIS MEDIA: CURRENT INSIGHTS INTO ACUTE, CHRONIC SUPPURATIVE, AND EFFUSIVE FORMS - Izabela Lekan; Michał Lenart; Klaudia Ostrowicz; Iwona Pudełko; Zuzanna Zięba; Kinga Kurenda (International Journal of Innovative Technologies in Social Science, 2025)
Otitis media, encompassing acute otitis media (AOM), chronic suppurative otitis media (CSOM), and otitis media with effusion (OME), is among the most prevalent pediatric disorders worldwide and a leading cause of medical consultations and surgical interventions in children. Acute otitis media is most common in infants and young children, with Streptococcus pneumoniae and non-typeable Haemophilus influenzae as the primary bacterial pathogens, often in association with viral infections. Management strategies vary according to disease type and severity, ranging from observation and antibiotic therapy to surgical approaches in complicated cases. Chronic suppurative otitis media represents a long-standing inflammatory condition characterized by persistent ear discharge and tympanic membrane perforation, frequently requiring surgical management such as tympanoplasty. Otitis media with effusion, in turn, is primarily associated with middle ear fluid accumulation and hearing impairment, often managed with tympanostomy tube insertion or adenoidectomy in recurrent or persistent cases. Preventive measures, especially pneumococcal vaccination, play an essential role in reducing the incidence of otitis media and its complications. Despite advances in diagnostics and treatment, the growing number of intratemporal and intracranial complications highlights the importance of early recognition, individualized therapeutic approaches, and interdisciplinary collaboration. In conclusion, effective management of otitis media requires integration of pharmacological, surgical, and preventive strategies, supported by evidence-based guidelines and further clinical research to optimize outcomes and reduce disease burden.